Procuring and Managing Adaptively: 5 Case Studies of Adaptive Mechanis ms - Pryor, Tony (2018)
Flexibility in program management is essential in all of the countries where USAID works. This is especially true in non-permissive environm ents (NPEs), where the ability to learn and adapt quickly to changing circumstances can help USAID staff members achieve their desired outco mes.